Synthesis and Characterizations of New 1,3-Oxazine Derivatives - Ozturkcan, S. Arda; Turhan, Kadir; Turgut, Zuhal (CHEM SOC PAKISTAN, 2011)
In this study, Betti's classical procedure, a Mannich-type aminoalkylation reaction of 2-naphthol with various aldehydes was applied in the presence of ammonia and then 1,3-disubstituted-2,3-dihydro-1H-naphtoxazines were synthesized. The structures of the obtained new compounds have been clarified by spectroscopic methods and confirmed with elemental analysis results. From the synthesized compounds, 1,3-Di(2-naphthyl)-2,3-dihydro-1H-naphto[1,2-e][1,3]oxazine was investigation of the effects of solvent and concentration with UV-Visible Spectrophotometer. Additionally, this compound was analyzed the mutagenic and anti-mutagenic properties.
Keywords: MUTAGENIC-ACTIVITY; Chemistry